Analysis of Competitiveness of Shallot (Allium cepa L.) Commodities in Nagari Alahan Panjang and Nagari Air Dingin Kecamatan Lembah Gumanti Kabupaten Solok, West Sumatera. - Komala Sari Nasution (Jurnal Food And Forest, 2021)
One of the horticultural commodities that has the potential to be well developed in Indonesia is the shallot commodity, which has the potential to be traded on the international market. The main producing province of shallots on the island of Sumatra is West Sumatra, Solok Regency. This study aims to determine the competitiveness of shallot farming in Solok Regency, West Sumatra and determine the impact of government policies on outputs and inputs in onion farming. The research method is descriptive qualitative and quantitative descriptive methods. Data analysis is PAM (Policy Analysis Matrix). The analysis shows that onion farming in Solok Regency, West Sumatra has a Private Advantage of 34,269,456.00 (Competitive Advantage) and has a Social Advantage of 92,203,432.00 (Comparative Advantage), and has a competitive advantage with a yield of 0.24 (Private Profitability) and comparative advantage with a result of 0.04 (Social Profitability). Keywords: competitiveness, policy analysis matrix, red onion